2018
DOI: 10.1097/nmd.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Eating Pathology Among Patients With Anorexia Nervosa and Bulimia Nervosa

Abstract: We sought to deepen our understanding of the relationship between pathological narcissism and eating disorders (ED) by examining specific facets that composed grandiose and vulnerable narcissism while taking into account self-esteem, a well-known and consistent risk factor for ED. Twenty-seven women diagnosed with anorexia nervosa (AN) and 23 women diagnosed with bulimia nervosa (BN) completed standardized measures of pathological narcissism, self-esteem, and dysfunctional eating attitudes and behaviors. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Several studies did not consider potential effects of medication. Many studies have not examined whether structural changes in the brain correlate with low self-esteem and self-evaluation, which are core features of BN and other eating disorders [11,12]. The present study aimed to help clarify the potential association of BN with altered GMV in the brain, and to examine whether these structural changes correlate with patient's self-evaluation.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies did not consider potential effects of medication. Many studies have not examined whether structural changes in the brain correlate with low self-esteem and self-evaluation, which are core features of BN and other eating disorders [11,12]. The present study aimed to help clarify the potential association of BN with altered GMV in the brain, and to examine whether these structural changes correlate with patient's self-evaluation.…”
Section: Introductionmentioning
confidence: 94%
“…The ability to exhibit control over emotional needs and relationships was correlated with AN-R in a comparison study involving individuals with AN and BN. However, the cross-sectional design was unable to determine whether this trait preceded AN-R and the sample size was relatively small [ 189 ].…”
Section: Personality Traits and Comorbid Mental Health Conditionsmentioning
confidence: 99%
“…Medium‐to‐large effect sizes were observed for the associations between maladaptive emotion regulation and EDs and eating‐related symptoms, specifically the relations between lack of emotional awareness, clarity, acceptance, reappraisal, problem‐solving, and EDs 36 . Another study examined pathological narcissism and revealed that hiding the self, which is a vulnerable narcissistic facet, significantly contributed to dysfunctional eating attitudes and behaviors over and above self‐esteem for women with AN 37 . Furthermore, vulnerable narcissism was associated with the use of rather maladaptive emotion regulation strategies, that is, suppression 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 Another study examined pathological narcissism and revealed that hiding the self, which is a vulnerable narcissistic facet, significantly contributed to dysfunctional eating attitudes and behaviors over and above self‐esteem for women with AN. 37 Furthermore, vulnerable narcissism was associated with the use of rather maladaptive emotion regulation strategies, that is, suppression. 38 This study indicated that emotion regulation is an important realm to improve not only for psychopathology but also for social functioning in patients with AN.…”
Section: Discussionmentioning
confidence: 99%